LANDSLIDE VULNERABILITY ZONE USING ANALYTICAL HIERARCHY PROCESS (AHP) METHOD IN BANYURESMI VILLAGE, SUKASARI DISTRICT, SUMEDANG, WEST JAVA - Ryonaldo Rizqi, Muhammad Ibrahim; Iskandarsyah, T. Yan Waliana Muda; Athallah, Muhammad Nabiel Nahensa; Renardi, Raditya Ahmad; Ganjar Gani, Reza Mohammad (Bulletin of Scientific Contribution, 2026)
Landslides are a common natural disaster in Indonesia, especially in Banyuresmi Village, Sukasari District, Sumedang Regency, which is a research area covering 9.58 . This study aims to identify landslide vulnerability zones using the Analytical Hierarchy Process (AHP) method. This method is used in decision making by compiling a process hierarchy structure, a pairwise comparison matrix, class and subclass weighting analysis, and a consistency ratio (CR) test. The method was applied to evaluate and spatially overlay the controlling factors of landslide vulnerability, namely slope gradient, lithology, aspect (slope direction), land cover, and distance from streams. The results showed that the study area was predominantly classified as having moderate to high vulnerability, with the high vulnerability zone covering 60.94% of the area, the moderate vulnerability zone covering 38.38%, and the low vulnerability zone covering only 0.68%. Slope gradient was identified as the dominant factor, followed by lithology and aspect. Field validation confirmed a strong spatial correlation between the mapped high-risk zones and the actual locations of reported landslides, demonstrating the reliability of the method through field validation. Overall, this study provides a scientific basis and recommendations for land use planning, minimizing the risk of landslides, and mitigation strategies, especially in residential areas in Banyuresmi Village.Keywords: Analytical Hierarchy Process, Banyuresmi, Landslide, Sumedang, Slope